2011
DOI: 10.1007/s13313-010-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of screening techniques and identification of new sources of resistance to Ascochyta blight disease of chickpea

Abstract: Abstract. Effective controlled-environment and field screening techniques were developed and refined to identify resistance to Ascochyta blight (AB), caused by Ascochyta rabiei (Pass.) Labr. in chickpea. A controlled environment plant growth room facility developed for AB evaluation at the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), Patancheru, India was modified to evaluate chickpea genotypes for resistance to AB. Controlled environment screening techniques, such as a seedling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 15 publications
2
63
0
1
Order By: Relevance
“…Sharma et al (2006) also found a high correlation between greenhouse (seedling stage) and field screening (adult plant) for AB resistance. This supports the evaluation for AB resistance using 10-day-old-seedlings in a controlled environment at ICRISAT and adult plant field screening at hot-spot locations in Dhaulakuan and Ludhiana in India (Pande et al 2009). Resistance to AB has been one of the major objectives in breeding programs.…”
Section: Discussionsupporting
confidence: 74%
“…Sharma et al (2006) also found a high correlation between greenhouse (seedling stage) and field screening (adult plant) for AB resistance. This supports the evaluation for AB resistance using 10-day-old-seedlings in a controlled environment at ICRISAT and adult plant field screening at hot-spot locations in Dhaulakuan and Ludhiana in India (Pande et al 2009). Resistance to AB has been one of the major objectives in breeding programs.…”
Section: Discussionsupporting
confidence: 74%
“…This facilitates the greatest discrimination among the lines in a trial. Screening techniques such as seedling screening and cut twig screening using excised trays are routinely being used to screen chickpea genotypes against AB in the controlled environment growth chamber facility at ICRISAT, Patancheru India [48]. Chen and Muehlbauer [49] developed a mini-dome technique for AB resistance screening and this technique is in use at Pullman, WA, USA.…”
Section: Genetic Resources Of Ab Resistancementioning
confidence: 99%
“…A resistant check/ susceptible was included in order to compare resistance of test entries with that of known resistant material [51]. A positive correlation between a field and controlled environment screening technique for AB was reported by Pande et al [48].…”
Section: Genetic Resources Of Ab Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…To overcome some of these genetic limitations for disease resistance in modern C. arietinum cultivars, resistance has been sought among wild relatives for a number of diseases (Singh et al 2008), including chickpea cyst nematode Heterodera ciceri (Di Vito et al 1996), and two important fungal diseases affecting chickpeas in Australia, namely Ascochyta blight (Collard et al 2001;Pande et al 2011) and Phytophthora root rot ). More specifically, Di Vito et al (1995) reported resistance to P. thornei in accessions of C. bijugum and C. judaicum (both in the secondary gene pool) and C. cuneatum Hochst.…”
Section: Introductionmentioning
confidence: 99%